Serum microcystin-LR levels and risk of gestational diabetes mellitus: A Chinese nested case-control study - Lin, Ying; An, Rongjing; Wu, Chunli; Liu, Huixia; Deng, Jing; Tan, Hongzhuan; Chen, Lizhang; Chen, Mengshi; Ma, Shujuan (Frontiers in Endocrinology, 2023)
Background: Previous experimental studies have reported an association between microcystin-LR (MC-LR) and glucose homeostasis, but the question of whether exposure to MC-LR is a risk factor for the pathogenesis of gestational diabetes mellitus (GDM) requires further epidemiological study. This study aims to explore the effects of MC-LR on GDM. Methods: A prospective nested case-control study was performed in the Hunan Provincial Maternal and Child Health Hospital (HPMCHH) in South China. A total of 119 patients with GDM and 238 controls were enrolled in the study. The chi-square test was used to compare the difference between the GDM group and the non-GDM group. Binary logistic regression was used to obtain odds ratios (ORs) by controlling for confounders. Results: The cumulative incidence of GDM in our sample was 13.7%. The detection rate of MC-LR in the GDM group were significantly higher than those in the control group (44.2% vs. 29.4%; p=0.007). Our results show that an elevated serum MC-LR level in the first trimester of pregnancy was related to an increased risk of GDM (OR: 1.924; 95% CI: 1.092-3.391; p<0.05). When stratified by age, educational level, parity, and passive smoking, significantly relationships were observed among those aged >30 years, lower income, higher education, none passive smoking, and more likely to be multiparous. Conclusions: Our data reveals that serum MC-LR level in the first trimester is independently associated with GDM.